Application Of Ornamental Typography On Stainless Steel Media as Decoration Of Angkringan Teapot - Hartono, Budi (Institut Seni Indonesia Yogyakarta, 2022)
Creativity in designing local Indonesian products needs to be carried out continuously in anticipation of the flood of imported products from various countries worldwide. The application of engraphing to industrial products strengthens the appearance of goods that have an impact on the quality of their value. This study aims to make innovations with stainless steel medium engraved on certain parts of the item so that the product looks more artistic. The effect produced is to adopt a typical angkringan teapot from the Klaten area. This research method is qualitative research combined with the design of the work. This research stage begins with data collection, data analysis, and presentation of analysis results. The analysis results are used as material for designing angkringan teapot products, which starts with extracting ideas, developing designs, and realizing outcomes.